Controlled Oxygenated Rewarming of Cold Stored Livers Prior to Transplantation: First Clinical Application of a New Concept. Issue 1 (January 2016) - Hoyer, Dieter P.; Mathé, Zoltan; Gallinat, Anja; Canbay, Ali C.; Treckmann, Juergen W.; Rauen, Ursula; Paul, Andreas; Minor, Thomas
Abstract : Background: Abrupt temperature shift from hypothermia to normothermia incurred on reperfusion of organ grafts has been delineated as a genuine factor contributing to reperfusion injury and graft dysfunction after transplantation. Methods: In a first clinical series of 6 patients, cold-stored livers, all allocated by the rescue offer mechanism by Eurotransplant, were subjected to machine-assisted slow controlled oxygenated rewarming (COR) for 90 minutes before engrafting. A historical cohort of 106 patients basically similar in graft (all rescue offer organs) and recipient factors was used for comparison. Results: The clinical benefit of COR was documented by a significant reduction by approximately 50% in peak serum transaminases after transplantation compared to untreated controls (AST 563.5 vs 1204 U/L, P = 0.023). After 6 months graft survival was 100% in the COR group and 80.9% in the controls ( P = 0.24). Respective patient survival was 100% and 84.7% ( P = 0.28). Real-time assessment of glucose concentration in the perfusion solution correlated well with postoperative synthetic graft function (r 2 = 0.78; P < 0.02). All treated recipients had normal liver function after a 6-month follow-up and are well and alive. Conclusions: This first clinical application suggests that controlled graft rewarming after cold storage is a feasible and safe method in clinical praxis and might become an adjunct in organ preservation. Abstract : Cold-stored livers were subjected to machine-assisted controlled oxygenated slow rewarming (COR) for 90 minutes prior to engrafting. This first clinical application suggests that COR after cold storage is a feasible and safe method and might become an adjunct in organ preservation.